147k views
0 votes
Q(x)=4x^2-1 find Q(-7)

Q(x)=4x^2-1 find Q(-7)-example-1

2 Answers

2 votes


Solution, \mathrm{Isolate}\:x\:\mathrm{for}\:If\left(I,\:x\right)Q\left(x\right)=4x^2-1:\quad x=(√(f\left(I,\:x\right)Q\left(x\right)I+1))/(2),\:x=-(√(f\left(I,\:x\right)Q\left(x\right)I+1))/(2)


Steps: If\left(I,\:x\right)Q\left(x\right)=4x^2-1


\mathrm{Switch\:sides}, 4x^2-1=If\left(I,\:x\right)Q\left(x\right)


\mathrm{Add\:}1\mathrm{\:to\:both\:sides}, 4x^2-1+1=If\left(I,\:x\right)Q\left(x\right)+1


\mathrm{Simplify}, 4x^2=If\left(I,\:x\right)Q\left(x\right)+1


\mathrm{Divide\:both\:sides\:by\:}4, (4x^2)/(4)=(If\left(I,\:x\right)Q\left(x\right))/(4)+(1)/(4)


\mathrm{Simplify}, x^2=(f\left(I,\:x\right)Q\left(x\right)I+1)/(4)


\mathrm{For\:}x^2=f\left(a\right)\mathrm{\:the\:solutions\:are\:}x=√(f\left(a\right)),\:\:-√(f\left(a\right)), x=\sqrt{(f\left(I,\:x\right)Q\left(x\right)I+1)/(4)},\:x=-\sqrt{(f\left(I,\:x\right)Q\left(x\right)I+1)/(4)},\sqrt{(f\left(I,\:x\right)Q\left(x\right)I+1)/(4)}=(√(f\left(I,\:x\right)Q\left(x\right)I+1))/(2),-\sqrt{(f\left(I,\:x\right)Q\left(x\right)I+1)/(4)}=-(√(f\left(I,\:x\right)Q\left(x\right)I+1))/(2)

The correct answer is
x=(√(f\left(I,\:x\right)Q\left(x\right)I+1))/(2),\:x=-(√(f\left(I,\:x\right)Q\left(x\right)I+1))/(2)

User Cheeaun
by
6.0k points
2 votes


q( - 7) = 4x {}^(2) - 1
so

4( - 7) {}^(2) - 1
195
User Treehouse
by
6.2k points